Models of acceptance of administrative decisions in the agroindustrial enterprises (Путеводитель предпринимателя, 2020)
In article the estimation of major factors of model of acceptance of the administrative decision is given, the estimation of a degree of quality of administrative decisions and the basic stages of formation of managerial process in agriculture is spent.